Measuring instrument for the perception of rural grouped school teachers - Almeida Molina, Lucía; Rodríguez Torres, Javier (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
After decades of oblivion of rural schools, as well as what is known as <<Empty Spain>>, recently, different people have made both more visible. Despite that, a long way to go is needed to fulfill the objective of providing rural schools with the importance they have. Therefore, through this research we are going to show a measurement instrument for the perception of rural grouped school teachers (from this point forward, CRA) in the Autonomous Region of Castilla-La Mancha. This has been validated, and it is applicable to other Autonomous Communities that have CRA.